Społeczno-środowiskowa perspektywa zagrożeń zdrowia pokolenia młodych dorosłych - Bulska, Joanna; Dworak, Alina (Chowanna, 2019)
The generation of the turn of the 20th/21st century is given to live in a new, changing reality. Modern, young generation entering adulthood is brought up in a post-transformation society, dominated by consumption, accelerated pace of life and threats occurring in all spheres of its functioning. In Poland, socio-cultural transformation has become for young adults not only a source of new challenges, opportunities, but also of threats. The consequences of the transformations are difficulties of (especially) the young generation in adapting to the ever-changing, unstable reality. The rapid changes in the surrounding reality have inspired research on the problems of growing up (including risky and harmful behaviours), and the difficulties of a generation growing up in an unstable reality.